Дополнительные сведения о бычках семейства Gobiidae кавказских рек бассейна Черного моря - Пинчук, В.И. (Вестник зоологии, 1974)
Parallel with certain constant morphological differences between populations of Gobius cephalarges constructor (Nord-m.) from the Sukhumi and Tuapse environs, differences in the male appearance are found in the period of spawning. The males from the Tuapse environs possess black colouration during protection of spawn which is not observed in mates of the Abkhazian populations. In areas of distribution of these two forms the area of distribution of the 3d form is interspersed. Its representatives are distinguished by compact trunk and less difference in dimensions of males and females. Populations from the Kura middle course are similar to the typical Abkhazian population The tributaries of the Kura lower reaches and small rivers of the Caspian Sea basin are inhabited with G. kessleri gorlap (11jin) but not with G. cephalarges constructor.